A Molecular Study with A Comparison of the Odds of Diagnostic Methods For Burkholderia Cepacia Bacteria Isolated from Patients with Diabetic Foot Ulcer - Waleed Dakhil Alnasrawy; Mahdi Hussain AL-Aammar (Indian Journal of Forensic Medicine & Toxicology, 2021)
The study aim to isolation and identification of Gram negative aerobic bacteria from clinical samples from various pathological conditions, investigation the virulence factors genes of bacteria. The present study included 250 specimens collected from patients suffering from diabetic foot ulcer , cystic fibrosis , people exposed to burns to different degrees , People with eye infections, in addition to those with fistulas , who attends to Alsader medical city, Al-Hakim General Hospital during the period extended from September 2020 to February 2021 for both sexes with an age ranged between )1 -75) years. The results revealed that 20 specimens of the total number of samples are Burkholderia cepacia . The results revealed that the frequency among males 198 (79.2%) more than female 52 (20.8%). The sample distribution according age, it appears high 7.6% with group 1-15 years in female , and high 22% with group 31-45 years in male, while high 26.8% with group 31-45 years male and female .